Information and Communications Technology (ICT) Literacy and Self-Efficacy of Junior High School Students: Basis for an ICT Enhancement Program - Hero, Jesson L. (Future Science / FSH-PH Publications, 2022)
The proliferation of science and technology in society allows learners to be more informed about the changes and developments in society and education. Moreover, literacy evolved from the conventional way of reading and writing to applying and accessing information from a digital environment. Hence, this paper aims to look into a way to extrapolate the correlation of Information and Communications Technology (ICT) literacy and self-efficacy of Junior High School students in one private school in the district of Obando, Bulacan, Philippines. Using a descriptive-correlation research design, the researcher believes a significant correlation between and among variables. The chosen respondents for the study consisted of one hundred and thirty-five (135). The findings of the study revealed that Junior High School students had moderate literacy towards ICT. Also, this study found out that the Junior High School students described their ICT self-efficacy as moderately agreeing. Furthermore, results of the correlational analysis using Pearson r revealed that the ICT literacy of Junior High School students was significantly correlated to their ICT self-efficacy. It is recommended that the schools include this area in their annual improvement plan under the students’ services affairs. Schools should pay attention to this since majority of the private schools now at the height of integrating ICT in the school system and further uplift the ICT literacy and self-efficacy of Junior High School students toward ICT integration through an enhancement program.